2020
DOI: 10.1101/2020.08.06.240119
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Radiolabelled Bacterial Metallophores as Targeted PET Imaging Contrast Agents for Accurate Identification of Bacteria and Outer Membrane Vesiclesin vivo

Abstract: Modern technologies such as 16s DNA sequencing capable of identifying microbes and provide taxonomic resolution at species and strain-specific levels is destined to be transformative1. Likewise, there is an emerging need to accurately identify both infectious and non-infectious microbes non-invasively in the body at the genus and species level to guide diagnosis and treatment strategies. Here, we report development of radiometal-labelled bacterial chelators, knowns as metallophores that allow non-invasive and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…A strategy of engineered EcN with exogenous reporter genes hSSTR2 has been reported for in vivo tumor visualization [ 49 ]. The outer membrane protein receptor FyuA of EcN can selectively recognize the 64 Cu and 89 Zr labeled metallophore yersiniabactin (YbT), which has a high affinity for transition metals [ 50 ]. A substantially higher PET signal was also observed in the EcN colonized tumor than that without the bacterial injection.…”
Section: Ecn-mediated Tumor Imagingmentioning
confidence: 99%
“…A strategy of engineered EcN with exogenous reporter genes hSSTR2 has been reported for in vivo tumor visualization [ 49 ]. The outer membrane protein receptor FyuA of EcN can selectively recognize the 64 Cu and 89 Zr labeled metallophore yersiniabactin (YbT), which has a high affinity for transition metals [ 50 ]. A substantially higher PET signal was also observed in the EcN colonized tumor than that without the bacterial injection.…”
Section: Ecn-mediated Tumor Imagingmentioning
confidence: 99%
“…Pastor et al presented a radiolabeling method 16 based on the classic stannous-chloride reduction of technetium. Siddiqui et al 17 describe a method for the radiolabeling of bacteria and OMVs for positron emission tomography (PET) based on the bacterial expression of FyuA, an outer membrane receptor for the metallophore yersiniabactin (YbT). They demonstrated that 64 Cu-labeled YbT can be incorporated into FyuA-expressing bacteria and their OMVs selectively.…”
Section: Introductionmentioning
confidence: 99%
“…Utilization of PET imaging for quantification of bacterial transport and attachment in column experiments first requires radiolabeling the bacteria with a positron-emitting radioisotope. Bacteria have been radiolabeled using two different approachessiderophore-derived chelators and a glucose analogue uptake . While these approaches are being developed for in vivo bacteria imaging in medicine, they have not yet been leveraged to study bacterial transport dynamics in environmental or geologic systems.…”
Section: Introductionmentioning
confidence: 99%